Reproduction and population structure of Achelous spinimanus (Crustacea: Portunoidea) in the northern coast of São Paulo, Brazil, and influence of environmental factors - Bernardo, Camila Hipolito [UNESP]; Bernardes, Veronica Pereira [UNESP]; da Silva, Thiago Elias [UNESP]; de Sousa, Aline Nonato [UNESP]; Taddei, Fabiano Gazzi; Fransozo, Adilson [UNESP] (Springer Nature, 2020)
We studied the reproduction and population structure of a population of Achelous spinimanus in the region of Ubatuba, Brazil. We collected them monthly, in 2000, in eight sites of different depths (5 to 40 m). The size at the onset of sexual maturity was estimated by the carapace width and the population structure was analyzed based on the size frequency distribution. In total, we collected 402 individuals: 28 juveniles, 105 males and 269 females. In 2000, A. spinimanus reproduced continuously and had a single peak in September–October. This timing contrasts with what has been observed in other populations and may be a local strategy to decrease the interspecific competition with other swimming crabs. The individuals of A. spinimanus from Ubatuba in 2000 were smaller (16.8–93.5 mm) than those from Fortaleza Bay (near Ubatuba) in 1988–1989 (19.0–97.3 mm). We suggest that intense trawling pressure may have contributed to a reduction in the size of individuals.
Keywords: Bycatch; Reproductive females; Ubatuba; “Siri-candeia”